Plan de negocios para la creación de una empresa dedicada a brindar un servicio integral de recreación y tareas dirigidas - Herrera Calderón, Luis Fernando (2019)
In order to evaluate the implementation of the business idea, the business plan is used, with the main objective of deciding on the implementation of a support center for school tasks in the Valle de los Chillos sector, in order to supply the need for parents to accompany their children in their school management. The target market consists of boys and girls between 5 and 10 years of age who have full-time father and mother and have the condition of spending alone in the afternoons in their homes or under the order of relatives. The development of the client is research shows that there is an existent need among fathers and mothers to cover their absence in home due to full-time work tasks; this aspect generates a strategy of focus to concentrate the marketing activities in communicating and promote the existence of this support center in tasks directed in Valle de los Chillos. The name assigned to the center is 123 Vamos a Jugar and its logo is based on geometric figures to give a fun image for children and transmit confidence to their parents. The organizational structure focuses on the management of the administrator who has several years of experience in the education sector; this person will be the core of the project, having the support of two teachers who will fulfill their tasks in the afternoon. The initial investment of the project is 22,087 dollars that is contributed by the shareholder of the center with a value of 16,565 dollars and 5,522 will be requested in Banco Pichincha at an annual rate of 16 percent of and payment period in five years. The recovery of this capital occurs between 3 and 4 years, obtaining a positive result in its indicators of net present value and internal rate of return of 17 percent of in the project flow, which is higher than its discount rate.